Propagação vegetativa e diversidade genética de inhame (Dioscorea sp.) - Santos, Crislaine Alves dos (2024)
The yam (Dioscorea sp.) is a crop with economic and alimentary importance for the Northeast region of Brazil. The low availability of propagative material with uniform sprouting and free of diseases is one of the limitations in commercial cultivation, thus, tissue culture emerges as an alternative technique for microtuber production. Furthermore, the development of conservation/use strategies for this genetic resource, managed by farmers, should be conducted through morphological and molecular characterization of yam germplasm to enhance the sustainability of the system. Thus, this study was conducted with the aim of evaluating the state of the art in two themes (vegetative propagation and genetic diversity), developing an in vitro propagation protocol, and estimating the genetic diversity among Dioscorea sp. genotypes from different states in the Northeast region of Brazil. The first chapter encompasses a systematic review with bibliometric analysis on the propagation and molecular characterization of the Dioscorea genus. The study examines which authors, journals, countries, and affiliations are more productive and which are the most developed and important topics in each research field. It was observed that Nigeria and China stood out, with publications on Dioscorea, and the most developed topics were tissue culture propagation and molecular characterization for estimating diversity and genetic structure. In the second chapter, the effect of sucrose, light spectra, and growth regulators on in vitro yam tuberization was studied to support the development of microtuber production protocols. Larger diameter (7.88 mm) and fresh weight (166.13 mg) were obtained by increasing sucrose concentration to 90 g.L-1 , while higher average fresh weight was observed for white and blue light spectra (320.4 and 276.8 mg, respectively) without the addition of CIN (0.0 mg.L-1 ) and with 1.0 mg.L-1 of ANA. The third chapter conducted a study to assess the genetic diversity among yam genotypes from different states in the Northeast region of Brazil, using morphological and molecular markers. Genetic diversity was estimated for 52 yam genotypes from Sergipe, Bahia, Alagoas, and Paraíba, using 31 morphological descriptors, SSR (Simple Sequence Repeat) and ISSR (Inter Sequence Simple Repeat) markers. High genetic diversity was observed among the evaluated genotypes, with low diversity among collection locations.